Pengembangan Sistem dan Dokumentasi Kelahiran Bayi - Daniel Jahja Surjawan; Sulaeman Santoso; Erico Darmawan Handoyo (Jurnal Teknik Informatika dan Sistem Informasi, 2023)
Every newly married couple will usually document whatever events they experienced to be remembered in the future. Especially when the process of giving birth will be a very happy moment. Documentation activities can be through photos or videos, sometimes also parents who save birth data by tearing up the calendar on the day of their child's birth and saving it in an album. Saving some of this data looks like can't be a complete of information, and often in a long time they won't pay attention to what they have stored, so data like piece of calendar will look outdated. In this research will develop the system and documentation of baby. The system will record every baby data that is born. In addition to birth data, photo documentation of the baby will also be stored. Furthermore, from all the data stored, a system will be created that can make a complete of documentation containing photos and details of the baby's birth data. The system that will be built is expected to increase value and satisfaction for patients, especially parents of babies with the services that the hospital provides, so that it can become a promotional for Kebonjati Hospital in establishing good relationships with patients